Media social literacy in Indonesian language teaching/learning at vocational high school - Nurmalina Nurmalina (Fakultas Ilmu Pendidikan UNP)
The disparagement of Indonesian language in academic sphere frequently occurs. The writing’s culture which must be grammatically and culturally correct has begun to fade away and the emergences of a variety of social media were the causes of this disparagement. Consequently, it weakened the learners’ reasoning ability and language skills. This study, therefore, aimed at identifying the causes of this disparagement where the locus of the research was at SMK Global Cendikia Kecamatan Tambang, Kampar, Riau. This study used sequential mixed methods of describing the causes. The results showed that the cognitive aspects were the focus on the Indonesian language learning; the ability of media literacy of SMK students on functional consuming literacy has been classified high, critical consuming literacy is low, functional presuming literacy was still categorized low, critical presuming literacy was low, and the low level of social media literacy ability of Indonesian learning success has not been maximally reached. It is, therefore, necessary to solve these problems by implementing learning strategies to improve the ability of good, correct and polite language and productive literary skills as well as to improve the ability of social media literacy students.